Kepastian Hukum Penanggulangan Tindak Pidana Penyeludupan Pakaian Bekas - Ario Putranto; Triono Eddy; Alpi Sahari (Mahesa Research Center, 2020)
The problem of smuggling both in terms of preventive, repressive and law enforcement in increasing the use of domestic production with a focus of discussion namely: how the Regulation is Related to the Criminal Act of Smuggling Used Clothes, how to Prevent the Criminal Acts of Smuggling of Used Clothes in Indonesia .. The research conducted is descriptive research. the normative juridical approach method is done by means of library studies. Data collection tools used in this study are data in the form of document studies and literature searches. which became the knife of analysis in this study was the theory of legal certainty, and the theory of criminal law policy. Regulations related to smuggling are regulated in Law number 10 of 1995 concerning Customs as amended by Law Number 17 of 2006, precisely in article 102 and article 102A, Decree of the Minister of Industry and Trade No. 642 / MPP / Kep / 9 / 2002 Concerning Changes to Attachment 1 Article 1 Decree of the Minister of Industry and Trade No. 229 / MPP / Kep / 7/1997 concerning General Provisions in the Import Sector. and also stated in Minister of Trade Regulation No. RI Minister of Trade Regulation No. 51 / M-DAG / PER / 7/2015 concerning the Prohibition of Imported Used Clothing. Mitigation of the crime of smuggling used clothing (by applying criminal law) carried out by investigators and / or PPNS is to conduct an investigation of smuggling activities.The problem of smuggling both in terms of preventive, repressive and law enforcement in increasing the use of domestic production with a focus of discussion namely: how the Regulation is Related to the Criminal Act of Smuggling Used Clothes, how to Prevent the Criminal Acts of Smuggling of Used Clothes in Indonesia .. The research conducted is descriptive research. the normative juridical approach method is done by means of library studies. Data collection tools used in this study are data in the form of document studies and literature searches. which became the knife of analysis in this study was the theory of legal certainty, and the theory of criminal law policy. Regulations related to smuggling are regulated in Law number 10 of 1995 concerning Customs as amended by Law Number 17 of 2006, precisely in article 102 and article 102A, Decree of the Minister of Industry and Trade No. 642 / MPP / Kep / 9 / 2002 Concerning Changes to Attachment 1 Article 1 Decree of the Minister of Industry and Trade No. 229 / MPP / Kep / 7/1997 concerning General Provisions in the Import Sector. and also stated in Minister of Trade Regulation No. RI Minister of Trade Regulation No. 51 / M-DAG / PER / 7/2015 concerning the Prohibition of Imported Used Clothing. Mitigation of the crime of smuggling used clothing (by applying criminal law) carried out by investigators and / or PPNS is to conduct an investigation of smuggling activities.